Effect of Serum Unbound Iron-Binding Capacity on the Tissue Distribution of 67Ga in Abscess-Bearing Rabbits - Scheffel, Ursula; Tsan, Min-Fu (Nuklearmedizin - NuclearMedicine, 1980)
The effect of serum unbound iron-binding capacity (UIBC) on the blood clearance and tissue distribution in abscessbearing rabbits was studied. In rabbits with low serum UIBC (95 ± 28 μg/dl), the blood clearance of 67Ga was much faster than that of rabbits with high serum UIBC (306 ± 27 μg/dl). The 67Ga uptake by the liver, spleen, kidney, muscle, bone marrow or abscess 24 hrs after injection was also much lower in rabbits with low serum UIBC. In contrast, the 67Ga deposition in bone was much higher in rabbits with low serum UIBC. Since the amounts of 67Ga in muscle and blood were disproportionally lower than that in the abscess, the abscess-to-muscle or abscess-to-blood ratio was much higher in rabbits with low serum UIBC than that of rabbits with high serum UIBC.